1999
DOI: 10.1038/sj.ijir.3900397
|View full text |Cite
|
Sign up to set email alerts
|

Intracavernosal self-injection therapy in men with erectile dysfunction: Satisfaction and attrition in 119 patients

Abstract: This study describes a 12 ± 24 month follow-up on 119 ED patients in an attempt to understand satisfaction with and dropout from ICI use. Results indicate 40% attrition, attributed primarily to a lack of ef®cacy of ICI, but also to spontaneous return of erectile function and to negative reactions surrounding the injection procedure. Multivariate analyses indicated that ICI dropouts were more likely to have co-existing premature ejaculation, low responses during psychophysiological screening, a lack of spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…4,5 Despite its efficacy, IC PGE 1 therapy is associated with patient-initiated discontinuation rates as high as 60%. [6][7][8][9] High discontinuation rates with IC vasoactive agents are attributable to a number of reasons, including penile pain and other complications of injection therapy, dislike of or difficulty with self-injection, fear of needles, poor response, change to alternate therapy, and lack of sexual spontaneity. [10][11][12] In contrast, in a large (n ¼ 979) 3-y extension study of sildenafil, in which most patients were receiving 100-mg doses, only 6.7% of patients discontinued for treatment-related reasons: 5.7% because of insufficient response and 1% because of treatment-related adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite its efficacy, IC PGE 1 therapy is associated with patient-initiated discontinuation rates as high as 60%. [6][7][8][9] High discontinuation rates with IC vasoactive agents are attributable to a number of reasons, including penile pain and other complications of injection therapy, dislike of or difficulty with self-injection, fear of needles, poor response, change to alternate therapy, and lack of sexual spontaneity. [10][11][12] In contrast, in a large (n ¼ 979) 3-y extension study of sildenafil, in which most patients were receiving 100-mg doses, only 6.7% of patients discontinued for treatment-related reasons: 5.7% because of insufficient response and 1% because of treatment-related adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…However, that needs confirmation by studies on human cavernous tissue. It is also tempting to speculate that similar phenomena could account for some intriguing findings such as the recovery of spontaneous erections reported by some ED patients after receiving several IC injections of PGE1 alone or associated with other erectogenic drugs, 4,[6][7][8][9]17 or the choice by some experienced patients to keep using oral PDE5 inhibitors and IC therapy in alternance. [18][19][20] In conclusion, we have demonstrated that even using a quite conservative treatment schedule, the efficacy of sildenafil, and likely of other PDE-5 inhibitors, can be enhanced to a clinically relevant level in a significant number of previously unresponsive patients by treating them with some programmed IC-PGE1 injections.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical viewpoint, this new treatment option could help to circumvent some of the difficulties frequently reported by intracavernous injection users such as the lack of spontaneity and naturalness of the sexual act that the procedure involves and its rejection by the partner. 5,[7][8][9] It would also reduce the risk of priapism, a complication occasionally observed in Programmed IC PGE1 for sildenafil nonresponse P Gutierrez et al patients taking IC injections and oral PDE-5 inhibitors within a short interval. 16 Regarding the possible biochemical mechanisms underlying this clinical effect, it is worth noting that significant crosstalk phenomena between the signal transduction pathways for cAMP (stimulated by PGE1) and cGMP (enhanced by PDE-5 inhibitors) are being increasingly documented both in human and animal cavernous tissue (reviewed in Steers 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracavernosal moxisylyte has produced success rates in 68% of patients (Buvat, BuvatHerbaut, Lemaire, & Marcolin, 1993). Despite these efficacies, long-term use of intracavernosal pharmacotherapies is poor, with dropout rates typically ranging from 50 to 80% (Barada & McKimmy, 1994;Rowland, Boedhoe, Dohle, & Slob, 1999). Reasons for discontinuation include declining sexual interest, inconvenience, cost, and preference for a less invasive form of treatment (Barada & McKimmy, 1994).…”
Section: Options For Treatmentmentioning
confidence: 97%